2017
DOI: 10.17233/sosyoekonomi.322057
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Bank-Specific and Macroeconomic Drivers Influencing Net Interest Margins of Turkish Listed Banks: Panel Data Evidence from Post-Crisis Era

Abstract: The aim of this study is to explore both the bank-specific and macroeconomic drivers of net interest margins using panel data techniques for a sample of 12 deposit banks publicly traded on the Borsa Istanbul over the post-crisis period 2010-2015. Our panel data results suggest that while bank size and managerial efficiency affect net interest margins negatively and significantly, operating cost, credit risk, and implicit interest payments influence the NIMs positively and significantly in the postcrisis era. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(137 reference statements)
2
5
0
Order By: Relevance
“…Findings are consistent with the extended dealership model proposed by Maudos and Solís (2009), who incorporated the bank's production function operating costs related to bank services by considering operating cost as a factor for stating the argument that operating cost needs to be covered even if the market power or risk of any kind is absent. The results are consistent with empirical studies that concluded that operational cost and bank margins are positively associated (Amuakwa-Mensah & Marbuah, 2015;Entrop et al, 2015;Fungáčová & Poghosyan, 2011;Işik & Belke, 2017;Lee & Isa, 2017;Nguyen, 2012;Poghosyan, 2013;Sun et al, 2014;Tarus et al, 2012).…”
Section: Empirical Results From Ab Gmm Estimatorsupporting
confidence: 91%
See 4 more Smart Citations
“…Findings are consistent with the extended dealership model proposed by Maudos and Solís (2009), who incorporated the bank's production function operating costs related to bank services by considering operating cost as a factor for stating the argument that operating cost needs to be covered even if the market power or risk of any kind is absent. The results are consistent with empirical studies that concluded that operational cost and bank margins are positively associated (Amuakwa-Mensah & Marbuah, 2015;Entrop et al, 2015;Fungáčová & Poghosyan, 2011;Işik & Belke, 2017;Lee & Isa, 2017;Nguyen, 2012;Poghosyan, 2013;Sun et al, 2014;Tarus et al, 2012).…”
Section: Empirical Results From Ab Gmm Estimatorsupporting
confidence: 91%
“…Several studies found a positive association of the capitalization ratio with bank margins (Amuakwa-Mensah & Marbuah, 2015; Angbazo, 1997;Asmar, 2018;Ben Naceur & Goaied, 2008;Doliente, 2005;Fungáčová & Poghosyan, 2011;Hijazeen, 2017;Lee & Isa, 2017;Maudos & Solís, 2009;Raharjo et al, 2014;Saunders & Schumacher, 2000;Williams, 2007), whereas Zhou and Wong (2008) and Gunter, Krenn, and Sigmund (2013) found a negative relationship with bank margins. Khawaja and Ud Din (2007), in the Pakistani context, and Işik and Belke (2017) in the Turkish context found the relationship to be insignificant.…”
Section: Degree Of Risk Aversionmentioning
confidence: 79%
See 3 more Smart Citations